Short-term structured dietary and exercise interventions delay diabetes onset in prediabetic patients: a prospective quasi-experimental study - Wang, Zhen; Qian, Li; Shen, Jian-Tong; Wang, Bing; Shen, Xu-Hui; Shi, Guo-Ping (Frontiers in Endocrinology, 2025)
HypothesisPrediabetes indicates an increased risk of developing diabetes mellitus. We hypothesized that structured anti-inflammatory and antioxidant dietary and exercise interventions (SAIDEs) can reduce the onset of diabetes in prediabetic patients.MethodsThis study included 542 prediabetic patients who met at least one of the three common criteria for prediabetes: fasting blood glucose (FBG), 2-h oral glucose tolerance (2h OGTT), or hemoglobin A1c (HbA1C). Patients were randomly assigned to one of four groups using the block randomization method: routine community intervention, dietary intervention, exercise intervention, or SAIDEs for 6 months. Follow-up assessments were conducted at 6 months and 7.5 years, monitoring diabetes-related outcomes, inflammatory markers, and diabetes progression.ResultsAt baseline, most tested variables, including age, gender, body weight, blood lipids, blood sugar, β-cell function, blood inflammatory and immunological markers, and energy intake, did not differ among the groups. After 6 months of short-term interventions (diet, exercise, and SAIDEs) and 6 months of follow-up, all intervention groups exhibited reduced total energy intake, body weight, blood pressure, blood cholesterol, and glucose levels, along with improved β-cell functions (all p < 0.001). Regardless of time considerations, intervention consistently increased total physical activity (p < 0.001). Short-term interventions also reduced blood IgE, high-sensitivity C-reactive protein, IL-6, and TNF-α, while increasing blood IL-4 and IL-10 (all p < 0.001). The prevalence of abnormal blood glucose markers—FBG, 2h OGTT, and HbA1C—significantly decreased within each intervention group after short-term intervention and 6 months of follow-up. The time-dependent Cox regression test did not indicate a significant effect of dietary or exercise intervention on diabetes incidence over the 8-year follow-up period. However, the log-rank test revealed significant differences in “survival” distribution among the four intervention groups (χ2 = 15.63, p = 0.001). The mean survival time before diabetes onset was significantly longer in prediabetic patients who received SAIDEs than in those in other groups.ConclusionsShort-term intervention with SAIDEs exhibited significant anti-inflammatory activity and reduced the prevalence of abnormal blood glucose markers. These benefits persisted even after 6 months of follow-up. However, over the 8-year follow-up period, intensive SAIDEs did not reduce diabetes incidence among prediabetic patients but did delay its onset.Clinical trial registrationhttps://www.chictr.org.cn/searchproj.html, identifier ChiCTR-IOR-16008445.